Formation, Losses, Preservation and Recovery of Aroma Compounds in the Winemaking Process - Bozena Prusova; Jakub Humaj; Jiri Sochor; Mojmir Baron (Fermentation, 2022)
A wine’s aroma profile is an important part of the criteria affecting wine acceptability by consumers. Its characterisation is complex because volatile molecules usually belong to different classes such as alcohols, esters, aldehydes, acids, terpenes, phenols and lactones with a wide range of polarity, concentrations and undesirable off-aromas. This review focused on mechanisms and conditions of the formation of individual aroma compounds in wine such as esters and higher alcohols by yeast during fermentation. Additionally, aroma losses during fermentation are currently the subject of many studies because they can lead to a reduction in wine quality. Principles of aroma losses, their prevention and recovery techniques are described in this review.